Fluorinated pyrrolidines and piperidines incorporating tertiary benzenesulfonamide moieties are selective carbonic anhydrase II inhibitors. (October 2015) - Le Darz, Alexandre; Mingot, Agnès; Bouazza, Fodil; Castelli, Ugo; Karam, Omar; Tanc, Muhammet; Supuran, Claudiu T.; Thibaudeau, Sébastien
Abstract A series of substituted pyrrolidines and piperidines were synthesized using superacid HF/SbF5 chemistry. Investigated as inhibitors of several human carbonic anhydrase (hCA, EC 4.2.1.1) isoforms, i.e. the cytosolic hCA I and II as well as the tumor-associated transmembrane isoforms hCA IX and XII, these compounds showed a never yet reported selectivity toward the human carbonic anhydrase hCA II. In the tertiary benzenesulfonamide family, this class of inhibitors points out a new mechanism of action for human carbonic anhydrase II inhibition.